2013
DOI: 10.20525/ijrbs.v2i1.59
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Institutional Supports for Women Entrepreneurship Development in Bangladesh: Achievements and Challenges

Abstract: Women’s entrepreneurship is important for women’s position in society, and for economic development of a country. Many scholars pointed out that women faces diverse challenges in doing business in a patriarchal society like Bangladesh. Women are now involved in economic activities than in the past, women constitute around 10 percent of the country's total business entrepreneurs. The present study is an effort to find out the factors which act as pull and push factors to engage women in ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Over the past two decades, Bangladesh has made substantial strides in enhancing the well-being of women and girls. With women constituting more than half of the country's population, their active involvement in socio-economic spheres has experienced a remarkable upswing [ 19 ]. Bangladesh stands as a beacon of women's empowerment and progress, setting an exemplary precedent through its dedicated efforts in this domain.…”
Section: Conclusion Policy Implications and Future Study Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, Bangladesh has made substantial strides in enhancing the well-being of women and girls. With women constituting more than half of the country's population, their active involvement in socio-economic spheres has experienced a remarkable upswing [ 19 ]. Bangladesh stands as a beacon of women's empowerment and progress, setting an exemplary precedent through its dedicated efforts in this domain.…”
Section: Conclusion Policy Implications and Future Study Scopementioning
confidence: 99%
“…Research on the social business fund by Ferdousi and Mahmud [ 15 ], challenges of women empowerment by Chowdhury and Rabbani [ 19 ], microcredit programs contribute to the development of women entrepreneurship by Chowdhury [ 20 ], training model for women entrepreneurship program by Idrus, Pauzi [ 21 ], factors affect the development of women entrepreneurship [ 22 , 23 ], factors influencing women's empowerment by Tabassum, Begum [ 24 ], sustainable development and women status [ 25 , 26 ], women empowerment for sustainable development in India by Lohani and Aburaida [ 18 ], were conducted. In Bangladesh, there is no primary data-based research regarding rural women empowerment through social media entrepreneurship and its relation to family income and sustainable development is not yet conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, entrepreneurs suffer from the loss of revenues as well as opportunities to improve their businesses for the future. Prior research has shown that corruption diminishes opportunities for franchising (Baena, 2012), high-growth entrepreneurship (Bowen and De Clercq, 2008), internationalisation of small businesses (Shirokova and Tsukanova, 2013), innovation (Anokhin and Schulze, 2009) and women’s entrepreneurship (Rabbani and Chowdhury, 2013). In addition, corruption can damage entrepreneurship by lowering employee job satisfaction (Phelps and Zoega, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women-owned businesses have been recognised as being vital to the overall growth of entrepreneurship, economic growth, poverty alleviation and job creation in many countries (Chirwa 2008;Maphalla, Nieuwenhuizen & Roberts 2009;Nmadu 2011;Brush & Cooper 2012;Rabbani & Chowdhury 2013), which is why Malebana (2017) noted that policy makers are focused on how economic growth via entrepreneurial activity can be stimulated.…”
Section: Introductionmentioning
confidence: 99%